2018
DOI: 10.1111/jpc.13925
|View full text |Cite
|
Sign up to set email alerts
|

Helmet use in bicycles and non‐motorised wheeled recreational vehicles in children

Abstract: Despite legislation mandating this, helmet use is not universal in cyclists, particularly younger riders. Even fewer NMWRV riders use them. To promote helmet use, a multifaceted approach aimed at altering community norms and individual behaviours and attitudes is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“… 4 6 12 13 15–17 In contrast, injuries involving the head in children have a greater risk of hospitalisation and mortality, and there is always the potential of lifelong negative effects for the patient. 18 The use of other equipment, such as elbow and knee pads, is estimated to be even lower. 12 13 15 …”
Section: Introductionmentioning
confidence: 99%
“… 4 6 12 13 15–17 In contrast, injuries involving the head in children have a greater risk of hospitalisation and mortality, and there is always the potential of lifelong negative effects for the patient. 18 The use of other equipment, such as elbow and knee pads, is estimated to be even lower. 12 13 15 …”
Section: Introductionmentioning
confidence: 99%
“…Rules vary wildly among states. A report of a study done to investigate reasons for increased ED visits among children in the United States showed that injuries were mainly related to the use of unpowered scooters [8]. Graph 1.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated trauma to the head could result in severe head injury. There are reports of severe head injuries sustained while riding unpowered scooters that resulted in permanent brain damage [7] [8]. Helmet use has been reported by the CPSC to reduce the risk of head injury by 80% [2].…”
Section: Severity Of Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we know that adolescents, especially males, will take more risks compared to younger children, and that higher proportions of adolescents have ATV-related crashes and injuries than those who are younger (Denning et al, 2014). Similar studies have shown many children, adolescents, and adults perceive riding a bicycle as not being very dangerous, and their risk of sustaining a head injury when bicycling without a helmet as "slight" (Finnoff et al, 2001;Ong et al, 2018).…”
Section: Attitudinal Barriersmentioning
confidence: 99%